Effect of Tension on Learner School Performance at Primary School Level at Bhakkar, Pakistan - Muzamil Hussain Al Hussaini; Dwi Sulisworo (Journal of Pedagogy and Education Science, 2022)
Effect of tension on students' school performance at the primary school level is a title of study work. Exploring the tension effect on learner performance at school is one of the study's key goals. A major factor in students' school success is tension. This study was intended to highlight the detrimental effects on students' academic performance. The study's objectives were to identify the types of tension associated with student performance, assess how tension affected learners' school performances, and distinguish between how tension affected learners of each gender differently. The researcher can offer a workable solution for the effect of tension on students' school performance to meet the study mentioned earlier objectives. Every primary school in the district of Bhakkar has provided information about this topic. For this study, ten primary schools were chosen randomly (n=10). The researcher subsequently split the ten primary schools (n = 10) into two groups (n = 5) of males and (n = 5) of females. The learner's academic and performance level is better in the case of low stress and anxiety. The main results of this study demonstrate that the teacher can play a crucial part in easing students' school anxiety, and also, this home is a prominent place where this can decrease.